Synthesis and characterization of palladium (II) pivaloyl thiourea complexes as homogeneous catalysts in sonogashira cross coupling reaction - Falynee Faha Abdul Wahab
Thiourea derivatives are gaining prominence due to its versatility as a ligand,insensitivity to air and moisture and can be designated by varying substituents on the nitrogen atoms. The coordination ability to transition metals has attracted interest to widely applied the derivatives in numerous fields. In this study, palladium (II)complexes featuring pivaloylthiourea derivatives were synthesized in order to evaluate their catalytic behavior in Sonogashira cross coupling reaction as homogeneous catalyst.